Helicobacter pylori the Latent Human Pathogen or an Ancestral Commensal Organism - Li, Jackie; Perez-Perez, Guillermo I. (Frontiers in Microbiology, 2018)
We dedicated this review to discuss Helicobacter pylori as one of the latest identified bacterial pathogens in humans and whether its role is mainly as a pathogen or a commensal. Prevalence of the diseases associated with this bacterium was highly prevalent during the XIX century and gradually has declined. Most diseases associated with H. pylori occurred in individuals older than 40 years of age. However, acquisition of H. pylori occurs mainly in young children inside the family setting. Prevalence and incidence of H. pylori has had a dramatic change in the last part of the XX century and beginning of the XXI century. In developed countries there is a clear interruption of transmission and the lowest prevalence is observed in children younger than 10 years in these countries. A similar decline is observed but not at the same level in developing countries. Here we discuss the impact of the presence or absence of H. pylori in the health status of humans. We also discuss whether it is necessary or not to establish H. pylori eradication programs on light of the current decline in H. pylori prevalence.